Gli1+ Cells Residing in Bone Sutures Respond to Mechanical Force via IP3R to Mediate Osteogenesis. (15th August 2021) - Huang, Xiaoyao; Li, Zihan; Liu, Peisheng; Wu, Meiling; Liu, An-qi; Hu, Chenghu; Liu, Xuemei; Guo, Hao; Yang, Xiaoxue; Guo, Xiaohe; Li, Bei; He, Xiaoning; et al.
Abstract : Early orthodontic correction of skeletal malocclusion takes advantage of mechanical force to stimulate unclosed suture remodeling and to promote bone reconstruction; however, the underlying mechanisms remain largely unclear. Gli1 + cells in maxillofacial sutures have been shown to participate in maxillofacial bone development and damage repair. Nevertheless, it remains to be investigated whether these cells participate in mechanical force-induced bone remodeling during orthodontic treatment of skeletal malocclusion. In this study, rapid maxillary expansion (RME) mouse models and mechanical stretch loading cell models were established using two types of transgenic mice which are able to label Gli1 + cells, and we found that Gli1 + cells participated in mechanical force-induced osteogenesis both in vivo and in vitro. Besides, we found mechanical force-induced osteogenesis through inositol 1, 4, 5-trisphosphate receptor (IP3 R), and we observed for the first time that inhibition of Gli1 suppressed an increase in mechanical force-induced IP3R overexpression, suggesting that Gli1 + cells participate in mechanical force-induced osteogenesis through IP3 R. Taken together, this study is the first to demonstrate that Gli1 + cells in maxillofacial sutures are involved in mechanical force-induced bone formation through IP3 R during orthodontic treatment of skeletal malocclusion. Furthermore, our results provide novel insights regarding the mechanism of orthodontic treatments of skeletal malocclusion.